Mortality of bullous pemphigoid in Singapore: risk factors and causes of death in 359 patients seen at the National Skin Centre. (1st June 2014) - Cai, S.C.S.; Allen, J.C.; Lim, Y.L.; Chua, S.H.; Tan, S.H.; Tang, M.B.Y.
Summary: Background: Bullous pemphigoid (BP) is the most common autoimmune‐mediated subepidermal blistering skin disease and is associated with significant morbidity and mortality. Objectives: To determine the 3‐year mortality rate, risk factors and causes of death in patients with BP in Singapore, compared with the general population. Methods: We conducted a retrospective cohort study of all newly diagnosed patients with BP seen at the National Skin Centre from 1 April 2004 to 31 December 2009. Demographic and clinical data on comorbidities and treatment were recorded. Mortality information was obtained from the National Registry of Diseases. Results: In total 359 patients were included in our study. The 1‐, 2‐, 3‐year mortality rates were 26·7%, 38·4% and 45·7%, respectively. The 3‐year standardized mortality risk for patients with BP was 2·74 (95% confidence interval 2·34–3·19) times higher than for the age‐ and sex‐matched general population. Parkinson disease, heart failure and chronic renal disease were associated with increased mortality, while combination treatment with low‐to‐moderate‐dose corticoste‐roids and immunomodulatory agents such as doxycycline and/or nicotinamide was associated with lower mortality. Overall, infections were the most common cause of death (59·8%), with the main causes of death being pneumonia (42·7%), cardiovascular disease (14·6%) and stroke (11·6%). Conclusions: This study confirms an increased 3‐year mortality rate for patients with BP in Singapore. Risk factors for increased mortality include medical comorbidities, especially neurological, cardiac and renal diseases. Treatment with combination therapy, including the use of low‐to‐moderate‐dose corticosteroid, appeared to decrease mortality risk in patients with BP.